Clinical and economic evaluation of the effectiveness of modern strategies for screening and early diagnosis of cervical cancer in the Russian Federation - Zh. V. Khaylova; V. V. Omelyanovskiy; R. A. Teryan; D. G. Shchurov; I. A. Mikhailov; Yu. I. Komarov; A. D. Kaprin (Опухоли женской репродуктивной системы)
Aim. To determine the most appropriate strategy for screening and early diagnosis of cervical cancer in the Russian Federation in terms of clinical (diagnostic) and cost-effectiveness.Materials and methods. To assess the clinical (diagnostic) effectiveness of various screening strategies, a systematic review of publications on studies evaluating the effectiveness of cytological examination and human papillomavirus (HPV) testing for the diagnosis of cervical cancer and its precancerous conditions was conducted. This analysis included publications on the results of studies that assessed the sensitivity and specificity of diagnostic tests used in screening programs. Economic evaluation of the use of various screening strategies was carried out using a mathematical model. The analysis is based on the Markov model of the natural development of oncogenic HPV infection in the absence of screening. Mathematical modeling was performed for a cohort of patients aged 30–64 years inclusive, who have not undergone hysterectomy and who initially have no symptoms of cervical cancer. Clinical and economic analysis was performed from the perspective of the Moscow healthcare system and taking into account the time horizon of 40 years. In a cost-effectiveness analysis, the costs and effectiveness of three screening strategies: conventional cytology followed by triage (p16 and Ki-67 expression detection, CINtec® technology); HPV testing (Cobas HPV®) followed by CINtec® triage and conventional cytology; co-testing – conventional cytology + HPV testing (Cobas HPV®) followed by CINtec® triage, were compared with a strategy of using conventional cytology alone.Results. The article presents the results of the evaluation of the clinical (diagnostic) efficiency of HPV testing compared with cytological studies, traditional cytological study compared with other diagnostic methods, HPV testing compared with other diagnostic methods, co-testing compared with cytological study only and the use of new biomarkers for the diagnosis of cervical neoplasia, including biomarkers for the detection of p16 and Ki-67 expression. Also, the analysis of cervical cancer screening programs in foreign countries, the efficiency of organized screening programs and the analysis of the cost-effectiveness of various screening strategies in Moscow are conducted. It has been established that there is no single model of cervical cancer screening in the world that would be suitable for every country. In most countries, there is a clear trend towards the transition from cytological testing to testing based on the detection of HPV DNA in certain age cohorts of women. It is also worth noting that not all developed countries have switched from opportunistic to organized cervical cancer screening. Based on the results of the clinical and economic study, it was determined that all the screening strategies studied are cost-effective, and the “Co-testing” screening strategy is the most effective in terms of reducing the number of cases of cervical cancer and deaths from cervical cancer.Conclusion. The co-testing strategy, including the use of a biomarker to detect the expression of p16 and Ki-67, should be considered as the main one for conducting screening and early diagnosis programs for cervical cancer in the Russian Federation.